2015
DOI: 10.1080/09168451.2015.1043118
|View full text |Cite
|
Sign up to set email alerts
|

Profilin 2 promotes migration, invasion, and stemness of HT29 human colorectal cancer stem cells

Abstract: We investigated the role of profilin 2 in the stemness, migration, and invasion of HT29 cancer stem cells (CSCs). Increased and decreased levels of profilin 2 significantly enhanced and suppressed the self-renewal, migration, and invasion ability of HT29 CSCs, respectively. Moreover, profilin 2 directly regulated the expression of stemness markers (CD133, SOX2, and β-catenin) and epithelial mesenchymal transition (EMT) markers (E-cadherin and snail). CD133 and β-catenin were up-regulated by overexpression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Both PFN2 [51] and IQGAP2 [52] regulate cell motility in response to intracellular signals. PFN2 is an epigenetic regulator of SMAD2/3 (Mothers against decapentaplegic homolog 2/3) [53], which in turn has been shown to promote metastasis in cancer cells [54]. SMAD2 and SMAD3 are also regulated by HIF-1α [55].…”
Section: Protein Association Network Identify Signaling Components Pmentioning
confidence: 99%
“…Both PFN2 [51] and IQGAP2 [52] regulate cell motility in response to intracellular signals. PFN2 is an epigenetic regulator of SMAD2/3 (Mothers against decapentaplegic homolog 2/3) [53], which in turn has been shown to promote metastasis in cancer cells [54]. SMAD2 and SMAD3 are also regulated by HIF-1α [55].…”
Section: Protein Association Network Identify Signaling Components Pmentioning
confidence: 99%
“…FOXD2-AS1 and PFN2 expression was positively correlated. Previous studies demonstrated that miR-150-5p and PFN2 were able to regulate the development of certain cancer types (33)(34)(35). miR-150-5p inhibits cancer cell aggressiveness by targeting SPARC (osteonectin), cwcv and kazal like domain proteoglycan 1 in head and neck squamous cell carcinoma (33).…”
Section: Discussionmentioning
confidence: 99%
“…The invasion assay was performed at 37 °C in a humidified atmosphere with 5% for 48 or 72 h. After incubation, the invasion assay was performed as the migration assay. Invasiveness was determined by counting cells with image J in three randomly selected microscopic fields per well …”
Section: Methodsmentioning
confidence: 99%
“…Invasiveness was determined by counting cells with image J in three randomly selected microscopic fields per well. [20][21][22]…”
Section: Migration and Invasion Assaysmentioning
confidence: 99%